SATISFACTION OF EMPLOYEES AT COVID-19 DEPARTMENTS - PEVEC, TEODOR optional (Medicinski časopis, 2024)
INTRODUCTION: Working conditions for health proffesionals can be greatly affected by pandemic caused by COVID-19. The aims of the study were to identify the level of job satisfaction  in  COVID-19 pandemic in hospital staff.METHODS: : This study was carried out in a convenience sample of nurses and medical doctors from four public regional Hospital in Slovenia. This was a cross-sectional survey study in which was used Short index of Job Satisfaction (SIJS). The questionnaire was completed by 110 participants. RESULTS: The sample mean score was 14.87±2.23. The item I feel fairly satisfied with my present job has high value (3.67). The is statistically significant differences in value by item Most days I am enthusiastic about my work between employees who work in COVID acute care department and COVID intensive care department (3.23:2.81). Younger employees have higher value by item I feel fairly satisfied with my present job than older employees. Medical doctors have higher value than registered by two items and registered nurses have higher value than medical doctors by one item.CONCLUSIONS: On most issues, the registered nurses have shown greater satisfaction than medical doctors.  With regular measurement of satisfaction, we can influence the change of team to have more satisfied employees.
Keywords: KEY WORDS: COVID 19-9, JOB SATISFACTION